The Diversity and Ecological Roles of Visitor Insects on Ganoderma sp. Fruiting Body - Vania Rasendriya Purbandini; Ananto Triyogo; Siti Muslimah Widyastuti (Institut Pertanian Bogor, 2025)
Pathogenic fungi's fruiting bodies may interact with other creatures such as insects. The purpose of this study was to better understand and identify the diversity of insect visits to Ganoderma sp. fruiting bodies, as well as their ecological responsibilities. From August to October 2022, this study was carried out at the Faculty of Forestry, Universitas Gadjah Mada Arboretum. Ganoderma sp. fruiting bodies were examined at three separate times: morning, afternoon, and evening. Insect visitor diversity was measured with diversity indices (H'), evenness (E'), and similarity (S'). A one-way ANOVA was used to investigate the effect of fruiting body category and observation period on insect abundance on fruiting bodies. The research findings revealed that the community of insect visitors to Ganoderma sp. fruiting bodies comprised 5 orders, 14 families, and 24 morphospecies. The dominant insect families were Schizopteridae and Meinertellidae, with dominant roles as predators (2 species), decomposers (2 species), and mycophages (4 species). Fruiting body categories influenced the families Scolytidae, Coccinelloidea, and Schizopteridae, but not Formicidae. The observation times indicated significant differences in the abundance of Scolytidae and Schizopteridae. Insects potentially serving as vectors carrying Ganoderma sp. fungal spores include Scolytidae, Coccinelloidea, Staphylinidae, Drosophilidae, Formicidae, and Schizopteridae. Information on visiting insects, especially those that potentially carry Ganoderma spp. spores, is crucial for understanding the spread of these fungal spores. This information can also aid in designing more effective control measures, including management of insect vectors. Keywords: community, insect activities, insects’ role, pathogen